THE ANALYSIS OF PSYCHOLOGICAL ASPECTS OF THE MAIN CHARACTER IN MOVIE “JOKER”BASED ON SIGMUND FREUD THEORY - Yustina Fitriani (Humanitatis : Journal of Language and Literature, 2019)
The aim of this research was to analyze the main characters on the movie “Joker” by Todd Phillips. This research were categorized as descriptive qualitative research. The data were taken by watching the movie and reading the scripts repeatedly.The theory of the psychological aspect is based on Sigmund Freud theory. They are the Id, ego, and superego. The main character’s Id is about his negative thought to the unfair life due to the negative response from his surrounding. It is a pleasure principle that works through primary process thinking. The main character’s ego is killing people who are wrong. It is a reality principle which works to satisfy all of the Id’s demand through secondary process thinking. The main character’s superego is keeping a good people alive. It is a moral principle that reflects to an idealistic standard through the rules of parents and society. Keywords:psychological aspects, main character, movie, Sigmund Freud Theory